Ion generation and loading of a Penning trap using pulsed laser ablation. (14th January 2020) - Sameed, Muhammed; Maxwell, Daniel; Madsen, Niels
Abstract: We investigated the production of aluminum and beryllium ions via pulsed laser ablation using 355 nm wavelength and 5 ns long laser pulses. The ablation threshold of Al + and Be + was measured to be 0.9 ± 0.1 (stat.) ± 0.3 (syst.) J cm −2 and 1.4 ± 0.1 (stat.) ± 0.4 (syst.) J cm −2 respectively. By employing electrostatic retarding potentials, the kinetic energy profile of the ablated ions was characterized as a function of laser fluence. Around the ablation threshold, we reliably produced between 10 8 and 10 10 ions, approximately 5% of which were dynamically trapped in a Penning–Malmberg trap.